AutoAsmaAlert: Technological tool to prevent Salbutamol Overuse in a Colombian Healthcare Provider "Letter to the Editor" - Miguel Angel Arroyo Alzate; Christian Adrián López-Castillo; Laura Bernal-Villada; Walberto Buelvas; Karen de Oro; Juan Camilo Rivera; Santiago Pinilla; Paula Garcia; Paola Rivero; Maribeb Almanza; Leonor Gonzalez (Health and Technology Journal (HTechJ), 2024)
The use of Salbutamol for the treatment of asthma has been a part of regular therapy as a short-acting β2-agonist since the 1960s. In the GINA 2024 guidelines, it is indicated that the use of salbutamol in monotherapy has been associated with increased mortality and poor asthma control. Therefore, the development of alternatives that allow rapid identification of its overuse is of great interest for the management of the disease. In order to achieve this objective, it was proposed to develop the technological tool, Auto Asthma Alerts “AAA”, with the aim to identifying in the clinical history and in real time the overuse of SABA (more than 3 inhalers per year) and thus alert physicians. The platform was successfully trialled on a pilot scale in a healthcare institution in Montería, Colombia, MediSinu IPS.